Milk scarcity hits the capital - Araya, E. (2012)
In this newspaper Dr Azage Tegegne’s (a scientist at the International Livestock Research Institute (ILRI) research showed that out of the 53.3 million cattle population, 10.6 million are milking cows. However, only 45pc of these cows can give birth and hence milk. The research furthermore indicated that out of the 10 million only around 300,000 are cross-breeds. The rest are local breeds which can only give 1 to 2 litres on average for a day. The United Nations World Health Organization (WHO) recommended that per capita consumption of milk should be 90 litres per year. For the total population of Ethiopia this would amount to a latest demand 7.2 billion litres a year.